A mixed-effects location scale model for time-to-event data: A smoking behavior application. (July 2019) - Courvoisier, Delphine; Walls, Theodore A.; Cheval, Boris; Hedeker, Donald
Abstract: In general, mixed-effects location scale models (MELS) allow assessment of within-person and between-person variability with time-to-event data for outcomes that follow a normal or ordinal distribution. In this article, we extend the mixed-effects location scale model to time-to-event data in relation to smoking data. Better understanding of the time-graded within-person variability of factors involved in nicotine dependence can be helpful to researchers in their efforts to fine-tune smoking cessation programs. We illustrate the MELS model with data on time to first cigarette measured every day for 7 days in smokers randomized to two groups: a) those asked to keep smoking, or b) those asked to stop. Our results show that some individuals remain very stable in their time to first cigarette over the week, while others show variable patterns. The stable individuals smoked every day, did not smoke immediately upon waking, and were all in the group asked to keep smoking. Conversely, the variable individuals had at least one day during which they did not smoke, other days during which they smoked within the first 5 min of waking, and they were almost all in the group asked to quit smoking. These findings suggested that MELS have the potential to provide insights on how people try to stop smoking. More importantly, this model can be applied to other clinically important outcomes such as time to relapse in a range of cessation programs. Highlights: MELS for time to event data are an extension of mixed effect models. MELS can answer questions on factors of between- and within-person variability. MELS is illustrated with a study of 851 smokers randomized to continue or quit smoking. Time to first cigarette was more variable among smokers asked to quit. Time to first cigarette was more variable from day to day among smokers asked to quit.